2015
DOI: 10.1177/0969141315591616
|View full text |Cite
|
Sign up to set email alerts
|

Availability of Advanced Breast Imaging at Screening Facilities Serving Vulnerable Populations

Abstract: Objective Among vulnerable women, unequal access to advanced breast imaging modalities beyond screening mammography may lead to delays in cancer diagnosis and unfavorable outcomes. We aimed to compare on-site availability of advanced breast imaging services (ultrasound (US), magnetic resonance imaging (MRI), and image-guided biopsy) between imaging facilities serving vulnerable patient populations and those serving non-vulnerable populations. Setting 73 United States imaging facilities across five Breast Can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…Not all studies demonstrated differences by socioeconomic status, specifically with inpatient imaging services utilization [39], myocardial perfusion imaging utilization [40], and on-site availability of advanced breast imaging and image-guided biopsy services [41]. However, in the case of inpatient imaging utilization, hospitalizations facilitate more timely workup given that the uninsured tend to receive less timely care and imaging services as an outpatient [39].…”
Section: Health Disparities In Radiologymentioning
confidence: 99%
“…Not all studies demonstrated differences by socioeconomic status, specifically with inpatient imaging services utilization [39], myocardial perfusion imaging utilization [40], and on-site availability of advanced breast imaging and image-guided biopsy services [41]. However, in the case of inpatient imaging utilization, hospitalizations facilitate more timely workup given that the uninsured tend to receive less timely care and imaging services as an outpatient [39].…”
Section: Health Disparities In Radiologymentioning
confidence: 99%
“…Over the last decade, new imaging-based breast cancer screening technologies have emerged, including tomosynthesis, screening (automated) ultrasound, and breast MRI, which are rapidly changing the landscape of breast cancer screening [9][2426]. These modalities show promise in improving sensitivity for detecting additional cancers when added to mammography, are FDA-approved, and are increasingly available in community settings [2730].…”
Section: Advanced Imaging Use Beyond Mammographymentioning
confidence: 99%
“…With the advent of new screening technologies, including digital breast tomosynthesis, screening ultrasound, and breast MRI, there is growing concern that existing disparities will worsen [9], since typically, vulnerable populations have been the last to benefit from new health technologies [10][11]. These newer screening modalities purport improved cancer detection over mammography alone, but are not offered at all screening facilities and often require a larger co-pay or out-of-pocket expense [12].…”
Section: Introductionmentioning
confidence: 99%
“…However, despite them, evidence continues to consistently demonstrate disparities among vulnerable women, such as those of low socioeconomic status and with insufficient health care access or insurance [8]. The issue may continue to be more pronounced for women affected by more than one of these factors, such as Medicaid beneficiaries [9,10].…”
mentioning
confidence: 99%